THE MEANING OF TYPOGRAPHY ON STREET FOOD CARTS IN BLOK M, SOUTH JAKARTA - Darsono, Boedhatmaka; Artayasa, I Nyoman; Setem, I Wayan; Arsa, I Ketut Sida (Yayasan Education and Social Center, 2026)
The phenomenon of changing trading patterns among street food vendors in Jakarta, from mobile to stationary stalls, has influenced the communication strategies used to attract consumers. While mobile carts rely on sound as a means of communication to signal their presence, stationary carts have shifted to visual communication through typography. This study uses mixed methods through observation, interviews, literature review, and documentation to examine the meaning of typographic elements on stationary carts in the Sisingamangaraja Street area, Blok M, South Jakarta. Semiotic analysis is used to interpret the relationship between the visual representation of typography and the meaning it produces. This study aims to reveal the meaning of visual typography elements on street food carts in both personal and communal dimensions. On a personal level, typography reflects the background, experience, and visual preferences of vendors as a form of individual identity. Meanwhile, at the communal level, typography functions as a collective representation that shapes the visual identity of the merchant group in the Sisingamangaraja street area, specifically in front of Blok M Plaza, South Jakarta. Through this interpretation, this study aims to provide a deeper understanding of the role of typography as a medium of visual cultural expression in the dynamics of the urban informal economy. The findings show that typography not only reflects the personal identity of traders, but also functions as a communal visual representation that shapes the identity of street vendor groups. This study confirms the role of typography as a medium of visual cultural expression in the context of the urban informal economy.